PENGARUH PEMBERIAN BEBERAPA KONSENTRASI URIN SAPI TERHADAP PERTUMBUHAN BIBIT KAKAO (Theobroma cacao L.) - Farid Hidayat; Husna Yetti; Sukemi Indra Putra (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The objective of the research was todetermine the effect of cow urineand getthe best concentration of cow urineon the growth of cocoa (Theobroma cacao L.). This study used Completely Randomized Design(CRD) consisting of concentrations cow urine treatment with 5 replications, in order to obtain 30 units of experiments in which each experimental unit contained three plant sand two plants used assampel.Eachtreatmentis: (U0) with out giving cow urine, (U1): giving of cow urine 30cc/literof water, (U2):giving ofcowurine35cc/literof water, (U3): giving ofcowurine40cc/literof water, (U4): giving of cowu rine 45cc/literof waterand(U5): giving ofcowurine50cc/literof water. Parameter observed were plant height (cm), number of leaves (strands), stem diameter (cm) , leaf area (cm2) and volume of plant roots (cm3). The results showedthat giving ofcow urinehas significant effect onplant height, numberof leaves, stem diameter, leaf areaandvolume of plant roots. Givingcow urineat a concentration of 35cc/literof water is the best concentration for all parameters tested. Seeing the effect ofcow urineon the research that has been done, the concentration of 35cc/literof wateris the best concentration on the growth ofcocoa age 4months. Keywords : Cocoa, cow urine, growth